COVID-19 infodemic: Fake news, real censorship. Information and freedom of expression in time of Coronavirus - Marsili, M. (Proceedings of Science&You 2021 Parallel Sessions, 2022)
Infection disease outbreaks are invariably characterized by myths and rumors, boosted by social media accounts, that media often pick up and circulate. On the grounds of protecting public health in the context of the covid-19 pandemic, some Member States of the Organization for Security and Co-operation in Europe imposed strict rules on the dissemination of “fake news”. This paper reviews the outbreak communication principles established by the World Health Organization and checks the compliance of emergency legislation, adopted under the pretext of combating misinformation and disinformation, against fundamental human rights.